An Adjustable Approach to Interval-Valued Intuitionistic Fuzzy Soft Sets Based Decision Making - Herawan, Tutut; Jasni, Mohamad Zain (2011)
Research on soft set based decision making has received much attention in recent years. Feng et al. presented an adjustable approach to fuzzy soft sets based decision making by using level soft set, and subsequently extended the approach to interval-valued fuzzy soft set based decision making. Jiang et al. generalize the approach to solve intuitionistic fuzzy soft sets based decision making. In this paper, we further generalize the approaches introduced by Feng et al. and Jiang et al. Using reduct intuitionistic fuzzy soft sets and level soft sets of intuitionistic fuzzy soft sets, an adjustable approach to intervalvalued intuitionistic fuzzy soft set based decision making is presented. Some illustrative example is employed to show the feasibility of our approach in practical applications.